Principles of economics : 3e - Shapiro, David; Greenlaw, Steven A.; MacDonald, Dan, 1985- (Houston, Texas : OpenStax, Rice University, 2022)
"Principles of Economics 3e covers the scope and sequence of most introductory economics courses. The third edition takes a balanced approach to the theory and application of economics concepts. The text uses conversational language and ample illustrations to explore economic theories, and provides a wide array of examples using both fictional and real-world scenarios. The third edition has been carefully and thoroughly updated to reflect current data and understanding, as well as to provide a deeper background in diverse contributors and their impacts on economic thought and analysis. For example, the third edition highlights the research and views of a broader group of economists. Brief references and deeply explored socio-political examples have been updated to showcase the critical - and sometimes unnoticed - ties between economic developments and topics relevant to students."--OpenStax.
Includes bibliographical references (pages 947-968) and index.
Catalography
Title from OpenStax ; viewed on March 23, 2023
Keywords: Economics -- Textbooks; Economics -- Research; Open educational resources; Textbooks